2017
DOI: 10.1002/term.2390
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy of autologous adipose mesenchymal stem cell-enriched, high-density lipoaspirate and topical timolol for healing chronic wounds

Abstract: Chronic venous leg ulcers are profoundly debilitating and result in billions in health care expenditure. Thus, there is a quest for engineered and innovative approaches. Herein we present a 63-year-old patient with a 30 year history of venous stasis and left lower extremity ulcers, which have been refractory to standard of care, anticoagulation and venous stripping. The medial ulcer was treated with transplantation of autologous adipose mesenchymal stem cell (AMSC)-enriched, high-density lipoaspirate (HDL) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 35 publications
0
19
0
1
Order By: Relevance
“…[64][65][66][67] Numerous case studies have also reported success in treating chronic, recalcitrant wounds with non-selective topical b-blockers such as timolol and propranolol. [68][69][70][71][72][73][74] Furthermore, two randomized controlled trials including 79 and 69 burn patients found that oral propranolol administration markedly decreases the time needed to receive skin graft and the area needed to be grafted. 75,76 Pyoderma gangrenosum Pyoderma gangrenosum is a rare, ulcerative inflammatory skin disorder with unknown aetiology.…”
Section: Wound Healingmentioning
confidence: 99%
“…[64][65][66][67] Numerous case studies have also reported success in treating chronic, recalcitrant wounds with non-selective topical b-blockers such as timolol and propranolol. [68][69][70][71][72][73][74] Furthermore, two randomized controlled trials including 79 and 69 burn patients found that oral propranolol administration markedly decreases the time needed to receive skin graft and the area needed to be grafted. 75,76 Pyoderma gangrenosum Pyoderma gangrenosum is a rare, ulcerative inflammatory skin disorder with unknown aetiology.…”
Section: Wound Healingmentioning
confidence: 99%
“…ASCs have been recognized to be highly biologically active, with regenerative roles in tissue formation, homeostasis, and immune regulation [3][4][5]. These unique properties render ASCs attractive in scenarios where the traditional approaches fall short of the desired therapeutic outcome, such as for chronic wounds, diabetic ulcers, osteoarthritis, ischemic heart disease, or type 1 diabetes, just to mention a few important areas [6][7][8][9][10]. Many ASC-based regimens have already progressed into clinical testing, and in the United States alone, more than 20 phase I and II clinical trials are currently being conducted (clinicaltrials.gov).…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has focused mainly on the ability of extracellular matrix (ECM)‐encapsulated stem cells to improve wound healing . However, fibrin may be suboptimal for such applications: it degrades quickly, requiring multiple treatment sessions; lacks intrinsic antimicrobial properties, which are needed to promote wound healing; and has limited ability to hold moisture.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has focused mainly on the ability of extracellular matrix (ECM)-encapsulated stem cells to improve wound healing. [7][8][9][10][11] However, fibrin may be suboptimal for such applications: it degrades quickly, requiring multiple treatment sessions 7 ; lacks intrinsic antimicrobial properties, which are needed to promote wound healing 12,13 ; and has limited ability to hold moisture. In contrast, well-defined synthetic hydrogels have emerged as promising vehicles for stem cell delivery because their 3D structure and high water content is ideal to support stem cell growth.…”
Section: Introductionmentioning
confidence: 99%